2017
DOI: 10.1111/cei.12934
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node and circulating T cell characteristics are strongly correlated in end-stage renal disease patients, but highly differentiated T cells reside within the circulation

Abstract: Ageing is associated with changes in the peripheral T cell immune system, which can be influenced significantly by latent cytomegalovirus (CMV) infection. To what extent changes in circulating T cell populations correlate with T cell composition of the lymph node (LN) is unclear, but is crucial for a comprehensive understanding of the T cell system. T cells from peripheral blood (PB) and LN of end-stage renal disease patients were analysed for frequency of recent thymic emigrants using CD31 expression and T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
(105 reference statements)
2
20
0
Order By: Relevance
“…Measuring TREC content by PCR yields an estimate of recent thymic emigrants in the circulation and indirectly of the thymus function. The expression of the CD31 molecule on the cell surface of RTE by flowcytometry is an easy alternative to TREC measurement and correlates well with this assay [7,[23][24][25]. After antigen-specific stimulation via the TCR, the T cell switches to a memory T cell phenotype.…”
Section: The Adaptive Immune Systemmentioning
confidence: 70%
See 1 more Smart Citation
“…Measuring TREC content by PCR yields an estimate of recent thymic emigrants in the circulation and indirectly of the thymus function. The expression of the CD31 molecule on the cell surface of RTE by flowcytometry is an easy alternative to TREC measurement and correlates well with this assay [7,[23][24][25]. After antigen-specific stimulation via the TCR, the T cell switches to a memory T cell phenotype.…”
Section: The Adaptive Immune Systemmentioning
confidence: 70%
“…Finally, not only intrinsic T cell factors may be involved but also environmental factors, as T cell proliferation after polyclonal stimulation is poor if performed in uremic serum [7] and the function of regulatory T cells also have been shown to be diminished [1]. The T cell composition in the secondary lymphoid organs of ESRD patients has been studied and in accordance with studies in individuals with normal renal function showed little presence of effector T cells [25]. There was a high correlation between numbers of naïve T cells in the lymph nodes and within the peripheral blood, indicating that the ESRD-related lymphopenia of naïve T cells is probably not caused by redistribution of these cells.…”
Section: Renal Failure and Adaptive Immunitymentioning
confidence: 71%
“…[6][7][8] Because of the logistical and ethical difficulties involved in acquiring human tissues, immunology studies have used surgical explants or biopsies of single sites derived from diseased tissues of small cohorts. [9][10][11][12][13][14][15][16] Results from such studies, while providing views into tissue immune cell populations, cannot be extrapolated to understanding baseline immune health in the diverse population.…”
mentioning
confidence: 99%
“…It has been hypothesized that these CD28memory T cells are responsible for the increased rejection risk of patients treated with belatacept [11,12]. This marker, also known as human natural killer-1 (HNK-1), is associated with cell-cell and/or cell-matrix interactions and is also correlated with end-stage renal disease and cytomegalovirus (CMV) infection [15][16][17][18][19]. This marker, also known as human natural killer-1 (HNK-1), is associated with cell-cell and/or cell-matrix interactions and is also correlated with end-stage renal disease and cytomegalovirus (CMV) infection [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of these CD28cells express CD57, a marker expressed by natural killer (NK) cells and T cells [13] which is used to identify terminally differentiated senescent cells with reduced proliferative capacity [14]. This marker, also known as human natural killer-1 (HNK-1), is associated with cell-cell and/or cell-matrix interactions and is also correlated with end-stage renal disease and cytomegalovirus (CMV) infection [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%